Model Business Process Reengineering dan Integrasi Pelaporan pada Pengendalian Intern - Dian Silviani; Ahmad Yani (Jejaring Administrasi Publik, 2022)
Internal control practices through assurance activities such as audits, reviews, evaluations, and monitoring; and consulting activities such as providing input, facilitation, and training have not been integrated with each other, thus affecting the effectiveness and efficiency of internal control.Â  Likewise, internal control reporting has not been integrated to external partners, which affects the quality of follow-up on the results of internal control activities. This study aims to initiate a model for implementing business process reengineering in integrating government internal control and finding a form of integrating internal control reporting to external partners to create certainty of follow-up on supervision results. The research method used is qualitative with a conceptual approach and case approach. The results showed that the business process reengineering model can be carried out by integrating assurance activities such as reviews, audits, evaluations, and monitoring with consulting activities such as providing advice, training, and agency facilitation into an integrated and connected system. The results also show the form of integrating agency performance reporting in integrated internal control in independent state institutions such as the Ombudsman and the State Civil Apparatus Commission, and an integrated internal control financial audit reporting system in independent state institutions such as the Corruption Eradication Commission and the Supreme Audit Agency. Keywords: Business Process Reengineering Model, Internal Reporting, Integration Control System